Одинокий русский: сборник детективов / перевод с английского С. Сергеева - Сергеева С. (Killer, 1992)
Экземпляры: ф.6 (2005) / Инвентарный номер: 48954 / Цена: / Сис.шифр: 84(0)-4 / Авт.знак: О-12 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-445.7